Use of propanediol to increase the production of dairy goats - Trujillo García, Abel Manuel; Hernández Castañeda, Mariana; Ducoing Watty, Andrés Ernesto; Alarcon Aburto , Adriana; Ceballos Escalante, Benito Joaquín Claudio (Spei Domus, 2025)
Introduction: An energy supplement (propanediol) was tested in a batch of multiparous dairy goats with 100 days of lactation and in one of the first-calving goats, compared with a batch of control goats in the same lactation period and number of parturitions under conditions of total stabling on a commercial farm in the Mexican Altiplano.Result: No significant statistical differences were found between the weight of the goats, body condition, and number of lactations (the batch of primals was handled separately). Regarding the average milk production, significant statistical evidence was found for the treated group with respect to the control group and the primal group.Conclusion: The difference in average milk between the treated group and the control group was 640 milliliters, which causes a sufficient economic gain to consider that applying propanediol in multiparous goats with 100 days of lactation is economically profitable.
Keywords: ruminants; energy; parameters; milk products